If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+6)=-2(x-2)
We move all terms to the left:
6(x+6)-(-2(x-2))=0
We multiply parentheses
6x-(-2(x-2))+36=0
We calculate terms in parentheses: -(-2(x-2)), so:We get rid of parentheses
-2(x-2)
We multiply parentheses
-2x+4
Back to the equation:
-(-2x+4)
6x+2x-4+36=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4
| (2x+18)+55+(4x+11)=180 | | 180+132=4x | | 7=b+116 | | 11=3/5(6x10) | | -11=5+3x | | 6(2x+2)=6x+30 | | 4x(26)=30 | | 0.5x=24.4 | | –6n−7=–7−6n | | 46-w=160 | | 25=-12a+49 | | 78.9183x+80.9169=79.904 | | -9x+1=9x+2 | | 11=3/5(6x=10) | | 25+107+x=180 | | (b+1)(b-6)=-12 | | 5j+-17=13 | | 1/4(-2v-24)=-3v-6 | | 3(x+1)+x=4(x+5)-13 | | –0.6=–0.2(g+–4) | | 1.1x=40 | | 49-0.3x=0.4+14 | | 102+x+43=180 | | 3(2q−1)=8q−5 | | 19x=-380 | | 8*2h=1÷ | | (2x+3)(x-11)(x/3+7)=0 | | 2-4x=2+2x-6x | | 2824=+x | | 5x^2+40x+18=-47 | | 3x-6+4=-2 | | -4x=12-20 |